1995
DOI: 10.1523/jneurosci.15-01-00376.1995
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal endotoxin exposure alters the development of the hypothalamic- pituitary-adrenal axis: early illness and later responsivity to stress

Abstract: The long-term consequences of neonatal endotoxin exposure on hypothalamic-pituitary-adrenal axis (HPA) function were assessed in adult female and male Long-Evans rats. At 3 and 5 d of age, pups were administered endotoxin (Salmonella enteritidis, 0.05 mg/kg, i.p.) at a dose that provokes a rapid and sustained physiological response, but with no mortality. As adults, neonatally endotoxin-treated animals exhibited significantly greater adrenocorticotrophic hormone (ACTH) and corticosterone responses to restraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
218
2
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(239 citation statements)
references
References 77 publications
10
218
2
9
Order By: Relevance
“…Neonatal effects-In 1995, Shanks et al reported that LPS given during the first week of life was associated with altered levels of glucocorticoid receptors in the rat brain (Shanks et al, 1995) and subsequent studies suggested that LPS pretreated animals were more responsive to adult LPS and exhibited reduced levels of inflammation to adjuvant-induced arthritis (Shanks et al, 2000). With the use of a similar neonatal LPS administration, Walker et al (2006) observed a marked attenuation in febrile response in nLPS (P3-5) treated males exposed to an adult LPS challenge, but no changes in CORT level was observed.…”
Section: Innate Immune Responsementioning
confidence: 99%
“…Neonatal effects-In 1995, Shanks et al reported that LPS given during the first week of life was associated with altered levels of glucocorticoid receptors in the rat brain (Shanks et al, 1995) and subsequent studies suggested that LPS pretreated animals were more responsive to adult LPS and exhibited reduced levels of inflammation to adjuvant-induced arthritis (Shanks et al, 2000). With the use of a similar neonatal LPS administration, Walker et al (2006) observed a marked attenuation in febrile response in nLPS (P3-5) treated males exposed to an adult LPS challenge, but no changes in CORT level was observed.…”
Section: Innate Immune Responsementioning
confidence: 99%
“…For example, Shanks et al (1995) and Shanks et al (2000) found differences in adult HPA axis function and responses to a model of experimentally induced arthritis when the rats were given LPS at P3 and P5. Hodgson et al (2001) also found alterations in adult physiology with a series of immune challenges given in the first week of life.…”
Section: Lps At P14 and P21 Alters Adult Febrile Responses To Lpsmentioning
confidence: 99%
“…These investigations all examined somewhat different end points from those looked at here and our present results indicate that this might be an important reason why these studies have found effects on the adult using such different preconditioning time points. In addition, the studies of Hodgson et al (2001), Shanks et al (1995) and Shanks et al (2000) used a multiple injection paradigm perhaps leading to effects on very different mechanisms.…”
Section: Lps At P14 and P21 Alters Adult Febrile Responses To Lpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endotoxin injection on as few as two occasions in the first week of life has been shown to exacerbate responses to stress much later in the mature animal, including HPA axis activation indicators (Hodgson et al, 2000;Shanks, Larocque, & Meaney, 1995), stressinduced suppression of lymphocyte proliferative responses (Shanks et al, 2000), and increased susceptibility to the metastasis of NK-sensitive MADB106 tumor cells (Hodgson et al, 2000). Neonatal endotoxin injection in rats has also been shown to result in delayed wound healing in the mature animal (Hodgson et al, 2000), which reflects the animals' inability to mount an inflammatory response (Padgett, Marucha, & Sheridan, 1998).…”
Section: Influences Of Endotoxin As the Stressor In Rat Studiesmentioning
confidence: 99%